2005
DOI: 10.1256/qj.05.85
|View full text |Cite
|
Sign up to set email alerts
|

Why does 4D‐Var beat 3D‐Var?

Abstract: SUMMARYA set of four experiments is described which measure the expected beneficial aspects of incremental fourdimensional variational (4D-Var) compared to 3D-Var data assimilation systems: allowing for the time of each observation in the full and increment fields with which it is compared, and using time-evolved covariances. Judging each scheme by the overall accuracy of resulting numerical weather prediction forecasts compared to observations, each aspect is shown to provide benefit.On other measures of anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(64 citation statements)
references
References 12 publications
1
63
0
Order By: Relevance
“…All occurrences of B in (15) appear as MBM T , which is identified as the propagation of B (which is itself valid at t 0 ) to time t by the linearized forecast model. This property, which is implicit in 4d-VAR, is one reason why 4d-VAR is superior to 3d-VAR (Lorenc and Rawlins, 2005), as it allows maximum gain from the manifestations of the B-matrix (sections 3.1-3.4) as the B-matrix will be more appropriate at each subsequent time than if the Bmatrix was not propagated. This is especially beneficial in cases where the evolving B-matrix becomes significantly different to the static B-matrix (e.g.…”
Section: Note About Background Error Propagation In 4d-varmentioning
confidence: 99%
“…All occurrences of B in (15) appear as MBM T , which is identified as the propagation of B (which is itself valid at t 0 ) to time t by the linearized forecast model. This property, which is implicit in 4d-VAR, is one reason why 4d-VAR is superior to 3d-VAR (Lorenc and Rawlins, 2005), as it allows maximum gain from the manifestations of the B-matrix (sections 3.1-3.4) as the B-matrix will be more appropriate at each subsequent time than if the Bmatrix was not propagated. This is especially beneficial in cases where the evolving B-matrix becomes significantly different to the static B-matrix (e.g.…”
Section: Note About Background Error Propagation In 4d-varmentioning
confidence: 99%
“…Thus, for simplicity, we chose 3DVar as the variation method. If observations are taken over an interval between analysis times, the higher-dimensional extension 4DVar has generally been shown to be more accurate (Lorenc and Rawlins, 2005 and Yang et al, 2009). Bonavita et al (2015) showed performance gains with the Hybrid-Gain method combining 4DVar and LETKF compared to using either alone when applied to the operational forecast system of the European Centre for Medium-Range Weather Forecasts (ECMWF).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the previous sequential methods, variational assimilation methods have been widely used in weather forecasting and costal engineering applications (Li and Navon, 2001;Seo et al, 2003;Valstar et al, 2004;Fischer et al, 2005;Lorenc and Rawlins, 2005;Seo et al, 2009;Lee et al, 2011aLee et al, , 2012Liu et al, 2012). In these methods, the cost function that measures the difference between the error in the initial conditions and the error between model predictions and observations over time is minimised to identify the best estimate of the initial state condition (Seo et al, 2009;Lee et al, 2011a).…”
Section: Data Assimilationmentioning
confidence: 99%